Drawing out critical thinking: testing the methodological value of drawing collaboratively. Issue 2 (3rd March 2016) - Knight, Linda; Zollo, Lyn; McArdle, Felicity; Cumming, Tamara; Bone, Jane; Ridgway, Avis; Peterken, Corinna; Li, Liang
Abstract : Early childhood research has long established that drawing is a central, and important activity for young children. Less common are investigations into the drawing activity of adults involved in early childhood. A team of adult early childhood researchers, with differing exposures and familiarities with drawing, experimented with intergenerational collaborative drawing with colleagues, students, family members and others, to explore the effectiveness of drawing as a research process and as an arts-based methodology. This testing prompted critical thinking into how drawing might facilitate research that involves young children, to operate in more communicable ways, and how research-focused drawings might occur in reference to a research project.